The mechanism of enterogenous toxin methylmalonic acid aggravating calcium-phosphorus metabolic disorder in uremic rats by regulating the Wnt/β-catenin pathway - Xing Fan; Jing Li; Yan Gao; Lin Li; Haisong Zhang; Zhaoyu Bi (Molecular Medicine)
Abstract Background Uremia (UR) is caused by increased UR-related toxins in the bloodstream. We explored the mechanism of enterogenous toxin methylmalonic acid (MMA) in calcium-phosphorus metabolic disorder in UR rats via the Wnt/β-catenin pathway. Methods The UR rat model was established by 5/6 nephrectomy. The fecal bacteria of UR rats were transplanted into Sham rats. Sham rats were injected with exogenous MMA or Salinomycin (SAL). Pathological changes in renal/colon tissues were analyzed. MMA concentration, levels of renal function indicators, serum inflammatory factors, Ca2+/P3+, and parathyroid hormone, intestinal flora structure, fecal metabolic profile, intestinal permeability, and glomerular filtration rate (GFR) were assessed. Additionally, rat glomerular podocytes were cultured, with cell viability and apoptosis measured. Results Intestinal flora richness and diversity in UR rats were decreased, along with unbalanced flora structure. Among the screened 133 secondary differential metabolites, the MMA concentration rose, showing the most significant difference. UR rat fecal transplantation caused elevated MMA concentration in the serum and renal tissues of Sham rats. The intestinal flora metabolite MMA or exogenous MMA promoted intestinal barrier impairment, increased intestinal permeability, induced glomerular podocyte loss, and reduced GFR, causing calcium-phosphorus metabolic disorder. The intestinal flora metabolite MMA or exogenous MMA induced inflammatory responses and facilitated glomerular podocyte apoptosis by activating the Wnt/β-catenin pathway, which could be counteracted by repressing the Wnt/β-catenin pathway. Conclusions Enterogenous toxin MMA impelled intestinal barrier impairment in UR rats, enhanced intestinal permeability, and activated the Wnt/β-catenin pathway to induce glomerular podocyte loss and reduce GFR, thus aggravating calcium-phosphorus metabolic disorder.